2016
DOI: 10.3109/14397595.2016.1168536
|View full text |Cite
|
Sign up to set email alerts
|

A novel method predicting clinical response using only background clinical data in RA patients before treatment with infliximab

Abstract: We have developed a novel method for predicting the clinical response using only background clinical data in RA patients before treatment with IFX. Our method for predicting the response to IFX in RA patients may have advantages over the other previous methods in several points including easy usability, cost-effectiveness and accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 19 publications
0
8
0
2
Order By: Relevance
“…Disease progression and outcome was a focus for 27 studies. Other considered issues were disease severity [72][73][74][75][76][77][78] in psoriasis, RA, IBD and coeliac disease; treatment response [79][80][81][82][83][84][85][86][87] in IBD, RA and primary biliary cirrhosis (PBC); and survival prediction [88][89][90] in PBC, RA and SLE. Other models focused on improved image segmentation to aid prognoses [91][92][93][94][95][96] for IBD and MS. Disease progression and outcome was the second-most prevalent area for model development.…”
Section: Disease Progression and Outcomementioning
confidence: 99%
“…Disease progression and outcome was a focus for 27 studies. Other considered issues were disease severity [72][73][74][75][76][77][78] in psoriasis, RA, IBD and coeliac disease; treatment response [79][80][81][82][83][84][85][86][87] in IBD, RA and primary biliary cirrhosis (PBC); and survival prediction [88][89][90] in PBC, RA and SLE. Other models focused on improved image segmentation to aid prognoses [91][92][93][94][95][96] for IBD and MS. Disease progression and outcome was the second-most prevalent area for model development.…”
Section: Disease Progression and Outcomementioning
confidence: 99%
“…Machine learning approaches have also been employed to generate treatment response algorithms. Miyoshi et al, (2016) reported that infliximab response could be predicted by using the 9 variables ESR, TJC, albumin, monocyte count, red blood cell number, prednisolone dose, methotrexate dose, HbA1c, and previous biologic exposure with 92 % accuracy [21]. However, these results were not confirmed in other anti-TNF cohorts and infliximab is rarely used in the UK because it has to be given intravenously compared to the subcutaneous route of other anti-TNFs.…”
Section: Clinical and Demographic Predictors Of Responsementioning
confidence: 99%
“…Man kann bei diesen Funktionen dabei aber nicht von einer Therapieempfehlung und im strengeren Sinne auch nicht von einer personalisierten Behandlung sprechen, da allgemeingültige Regeln angewendet werden. Bereits 2016 erreichte ein neuronales Netzwerk zur Vorhersage auf das Ansprechen auf Infliximab eine Accuracy von 92 % mit nur 9 klinischen Variablen [24]. Auch die Entscheidung zur Infliximab-Dosiseskalation konnte durch maschinelles Lernen effizient klassifiziert und damit vorhergesagt werden [25].…”
Section: Automatisierte Klinische Entscheidungssysteme In Der Rheumatologieunclassified